The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fneur.2020.483570
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Dyslipidemia Management for the Prevention of Ischemic Stroke Recurrence in China

Abstract: Background: The benefit of blood cholesterol reduction for secondary prevention of ischemic stroke remains undetermined in Chinese patients. The purpose of this meta-analysis was to determine whether lipid-lowering agents including statins, fibrates, nicotinic acid, and ezetimibe reduced the risk of recurrent stroke in ischemic stroke patients in China and whether such findings could inform treatment decisions for blood lipid-lowering treatment in China.Methods: The English electronic databases PubMed, EMBASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…A meta-analysis showed that reducing 1mmol/L LDL cholesterol reduces the risk of stroke by 21.1% [ 18 ]. Another meta-analysis showed similar results in reducing the incidence of new events [ 19 ] and re-occurrence of stroke [ 20 ] using statin therapy. However, it showed no significant reduction in fatal stroke with statin therapy [ 19 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A meta-analysis showed that reducing 1mmol/L LDL cholesterol reduces the risk of stroke by 21.1% [ 18 ]. Another meta-analysis showed similar results in reducing the incidence of new events [ 19 ] and re-occurrence of stroke [ 20 ] using statin therapy. However, it showed no significant reduction in fatal stroke with statin therapy [ 19 ].…”
Section: Discussionmentioning
confidence: 92%
“…It is important to take dyslipidemia as a risk factor along with other modifiable risk factors. Multiple meta-analyses have established that reducing LDL cholesterol reduces the overall risk of stroke [ 20 ]. Statins are the first-line medications for dyslipidemia, and other options include fibrates, ezetimibe, and PCSK9 inhibitors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statins, as the most important lipid-lowering drugs, can greatly reduce the risk of cardiovascular events either as a therapeutic or preventive medication [45]. For instance, it was found that the use of a lipid-lowering drug leads to 21 % decrease in ischemic stroke [46]. A 50 % or more reduction in LDL-C profoundly reduced the risk of ischemic stroke recurrence (OR 0.15, 95 % CI 0.11-0.20) in this study [46].…”
Section: Dyslipidemiamentioning
confidence: 99%
“…The primary abnormalities are the increasing levels of total cholesterol, lowdensity lipoprotein (LDL), and triglycerides (TG), as well as the decreasing level of high-density lipoprotein (HDL) [4]. Further, this disease is caused by lipid metabolism disruption due to genetic and environmental factors, and it becomes one of the risk factors of stroke [5,6]. Generally, stroke, which attacks the brain, occurs suddenly, progressively, and quickly because of local and/or global disruption of nerve function [7].…”
Section: Introductionmentioning
confidence: 99%